El Excentrico, 1964-12-05 - Garcia, Humberto:::Publisher:::::::::::: (San Jose, California; Garcia Printing, 2023)
December 5, 1964 [5 de diciembre de 1964] Ano 15, No 4. Cover has a signed photograph of actress and singer Libertad Lamarque.